Analisis Anomali Gravity Daerah Panas Bumi Non-Vulkanik Di Bangka Tengah (Studi Kasus Panas Bumi Terak dan Keretak) - Gusnia, Eri; Kusmita, Tri; Indriawati, Anisa (Jurusan Fisika, Universitas Bangka Belitung, 2022)
Central Bangka is one area that has geothermal potential such as the Terak and Keretak area. These area have hot spring manifestation. Geothermal manifestations in Bangka is the type of non-volcanic radiogenic geothermal. Origin sources of this manifestation suspected from rocks run into the crack, folds and faults. The purpose of this study was to identify rock speading in geothermal area and it’s correlation between geothermal manifestation in Terak and Keretak. The data obtained from the TOPEX/Poseidon satellite is in the form of FAA (Free Air Anomaly) data. The data is then corrected using Burger correction and field correction. Spectral analysis was performed by Fourier transform with moving average filter. The results showed that Complete Bouger Anomaly has 13 mGal-39 mGal. Regional anomaly has 5,4 mGal - 9.8 mGal. Residual anomaly has 7 mGal sampai 29 mGal. There area was consist of intrusive granite rock from the Granite Klabat formation, clas and sandstone from Tanjung Genting Formation. Gravity anomaly shown Geothermal Terak and Keretak are composed of the same distribution of rock.